Interaction dynamics of upstream vortex with vibrating tandem circular cylinder at subcritical Reynolds number. (November 2017) - Mysa, R.C.; Law, Y.Z.; Jaiman, R.K.
Abstract: This numerical study investigates the local unsteady characteristics of transverse wake-induced vibration (WIV) of an elastically mounted downstream circular cylinder in a tandem arrangement at subcritical Reynolds number regime of 5000 ≤ R e ≤ 10000 . The upstream cylinder with an equal diameter is kept fixed and the downstream one is free to vibrate in a direction perpendicular to the freestream flow with a low mass damping parameter m ∗ ζ = 0 . 018, where m ∗ is mass ratio and ζ is damping. Similar to the recent experiment study, we consider a longitudinal separation L x ∕ D = 4 . 0 in the co-shedding regime, where L x denotes the center-to-center distance and D is the diameter of cylinder. In the present study, we perform three-dimensional simulations to further shed light on the sustained low frequency motion and the larger amplitude of downstream cylinder interacting with a turbulent vortical wake. We employ a nonlinear partitioned iterative scheme and a dynamic subgrid-scale model based on variational formulation for simulating the fluid–structure interaction in a turbulent wake. We assess the transverse amplitude and the frequency response against the experimental measurements for the reduced velocity U r ∈ [ 4, 14 ], whereby the reduced velocity is adjusted by changing the freestream Reynolds number. Of particular interest is to study the interaction of freely vibrating downstream cylinder with upstream vortices and the role of stagnation point movement in the transverse load generation over the downstream cylinder. We examine instantaneous energy transfer from the fluid flow to the vibrating downstream cylinder with respect to the movement of stagnation point and the vortex–structure interaction. We compare the WIV response of downstream cylinder against the isolated cylinder with prescribed periodic motion in a freestream flow. Through the vorticity contours and pressure distribution, we finally investigate the upstream vortex interaction with the vibrating downstream cylinder during the oscillation cycle of wake excitation. Highlights: Interaction dynamics of vortex with vibrating downstream tandem cylinder. Role of stagnation point and boundary layer movement on wake excitation. Movement of boundary layer causes low frequency wake excitation. Analogous forced vibration results to deduce stagnation point dynamics. Validation of fluid–structure solver with dynamic subgrid LES.